Outpatient (same‐day discharge) versus inpatient parotidectomy: A systematic review and meta‐analysis. (26th March 2020) - Flach, Susanne; Hey, Shi Ying; Lim, Alison; Maniam, Pavithran; Li, Zhi; Donnan, Peter T.; Manickavasagam, Jaiganesh
Abstract: Background: Parotidectomy is often performed as an inpatient procedure largely due to drain insertion; however, outpatient parotidectomy has increasingly become an attractive alternative for its shorter hospital stays and greater efficiency in cost‐effectiveness. Objective of review: To assess the safety and feasibility of outpatient (or same‐day discharge) parotidectomy compared with inpatient parotidectomy. Type of review: Systematic review of the literature and meta‐analysis, in accordance with the PRISMA guidelines. Methods: Pubmed/Medline, Embase, CINAHL, Google Scholar, Web of Science, The Cochrane Library, Cochrane Central Register of Controlled Trials (CENTRAL) were searched for articles published in English between 01/01/1990 and 05/10/2019. The Newcastle‐Ottawa Scale was used for quality assessment and Review Manager 5.3 for meta‐analyses. Main outcome measures: Primary outcomes assessed were postoperative complications including bleeding/haematoma, surgical site infection, seroma and facial weakness. Secondary outcome was readmission rate. Results: Out of 445 studies identified, 6 were selected for systematic review. The overall quality of evidence was moderate. A total of 3664 patients were included (1646 in the outpatient group and 2018 in the inpatient group). Comparing the outpatient with inpatient cohorts, there were lower complications in outpatient groups though not statistically significant for haematoma (OR = 0.45; 95% CI = 0.11‐1.92; P  = .28), surgical site infection (OR = 0.88; 95% CI = 0.46‐1.69; P  = .70), seroma (0.79; 95% CI = 0.21‐3.03; P  = .74), facial nerve weakness (OR 0.39; 95% CI = 0.14‐1.08; P  = .07) and hospital readmission (OR 0.58; 95% CI = 0.33‐1.04; P  = .07). Conclusions: Outpatient parotidectomy appears to be safe and compares favourably to inpatient procedure in postoperative complication and readmission rates.